Adherent vs. Free-Floating Neural Induction by Dual SMAD Inhibition for Neurosphere Cultures Derived from Human Induced Pluripotent Stem Cells - Pauly, Martje G.; Krajka, Victor; Stengel, Felix; Seibler, Philip; Klein, Christine; Capetian, Philipp (Frontiers in Cell and Developmental Biology, 2018)
Keeping neural stem cells under proliferation, followed by terminal differentiation, can substantially increase the number of neurons generated. With regard to the usability of proliferating neurospheres (NSPHs) cultures, adherent induction protocols have not yet been studied in comparison to embryoid body (EB)-based protocols. To compare these proctocols, neural induction of human induced pluripotent stem cells was performed by dual SMAD inhibition under both adherent and free-floating EB culture conditions. After 10 days, we transferred cells to low-attachment culture plates and proliferated them as free-floating neurospheres. RNA was collected, transcribed to cDNA and analyzed for sonic hedgehog expression that plays an important role during proliferation process. NSPHs were analyzed by immunofluorescence imaging directly and upon continueddifferentiation. The EB-based approach yielded in higher numbers of cells expressing the neural stem cell marker Nestin, and showed in contrast to the adherent induction protocol increasedexpression levels of sonic hedgehog. Although improvements to culture consistency and reliability are desirable, the EB-based protocol appears to be superior to the adherent protocol for both, the proliferation and differentiation capacity.